แนวทางการพัฒนากลยุทธ์ทางการตลาดของกลุ่มวิสาหกิจชุมชนศูนย์การเรียนรู้ไม้ดอกไม้ประดับ กรณีศึกษาหมู่ที่ 9 ตำบลบ้านโพธิ์ จังหวัดสุพรรณบุรี - จอมพงษ์, วรรณิสา; แสนภูมี, สมชัย (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 1 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 1 : มกราคม - เมษายน 2568, 2025)
This study aimed to: 1) the marketing challenges of the Community Enterprise Learning Center for Ornamental Plants in Moo 9, Suphan Buri Province, 2) develop appropriate marketing strategies. A qualitative research approach was employed, using in-depth interviews and focus group discussions with 14 community enterprise members and business owners. Data were analyzed using the 4P’s marketing mix and SWOT analysis, leading to strategy formulation through the TOWS Matrix. The findings revealed key challenges, including reliance on traditional sales channels, lack of digital marketing knowledge, and intense competition from larger enterprises. While the group excels in product quality, weaknesses in market management persist. Proposed strategies include online marketing promotion, product and packaging development, competitive pricing, and business networking. This study provides a framework for similar community enterprises to enhance their marketing strategies, improve competitiveness, and ensure long-term business sustainability.